Comic reading as a tool for improving mental health and English language proficiency - Zanyar Nathir Ghafar; Omar Mohammad-Ameen Ahmad Hazaymeh; Yusuf Sarkingobir; Abubakar Muhammad Dikko; Aprianoto Aprianoto; Amrullah Amrullah; Majid Wajdi (Journal of Education, Social & Communication Studies, 2026)
This study aims to explore the role of comic reading in improving mental health and enhancing English language learning among students and young readers. Comics are increasingly recognized as educational and psychological tools because they combine visual narratives, contextual language, and emotional expression in an engaging format. The study employs a qualitative document review method by analysing journal articles, books, and previous studies related to comics, mental well-being, and English language acquisition. The collected data were analysed using descriptive and thematic analysis to identify the educational and psychological benefits of comic reading. The findings reveal that comics contribute positively to readers’ mental health by reducing stress, increasing motivation, and fostering emotional connection through relatable stories and characters. In language learning, comics help improve vocabulary mastery, reading comprehension, speaking confidence, and contextual understanding of English expressions. The visual support provided in comics also assists learners in understanding meaning more effectively and maintaining learning interest. In conclusion, comics serve not only as entertainment media but also as valuable resources for supporting emotional well-being and developing English language skills. The study suggests that educators integrate comics into language learning activities to create more enjoyable and meaningful learning experiences.